Positive and negative affectivity as mediators of volunteerism and service-oriented citizenship behavior and customer loyalty - Jain, Ajay K. (2014)
This study sought to examine the impact of volunteerism (motivation to help) on service-oriented organizational citizenship behavior (S-OCB) of salespeople as mediated by the positive and negative affectivity, and further how the involvement of salespeople in S-OCB would affect the customer loyalty toward the company. The context chosen for empirical investigation was the Indian pharmaceutical sector and the sample consists of 125 medical sales representatives from four companies that are well-established players, including three multinational firms and one Indian company, as well as their supervisors (n = 48) and doctors (n = 150). The data are analyzed through partial least squares approach to path modeling to estimate the measurement and structural parameters. All of the hypotheses are confirmed. The results of this study indicate that volunteerism exhibits a significant positive impact on S-OCB and customer loyalty. In addition, this positive impact is partially mediated by positive and negative affectivity. In sum, the proposed model explains a large amount of variance in S-OCB and customer loyalty, suggesting that it will serve as a useful tool for analyzing service-oriented organizational sale persons’ behavior and customers’ reactions. The implications of these results include improving service OCB by promoting volunteerism in the service industry and emphasizing the important roles of service staff in enhancing the customer loyalty.